THE ENVIRONMENTAL IMPACT OF THE DIGITAL FINANCIAL INCLUSION: THE CASE OF THE REPUBLIC OF SERBIA - Latinovic, Milica; Dmitrovic, Veljko; Benkovic, Sladjana (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2022)
Climate change is one of the most important issues in today’s world. To address this matter, countries and companies are trying to become more sustainable. Countries have set the targets for greenhouse gas emissions reduction, which cannot be reached without the joint effort of the retail, small, medium, and corporate sector. Moreover, emissions and pollution reductions can be achieved through the economic and social development. Digitalization proved to be a fast-track for the economic growth and green development. That fast track becomes even faster if the country’s financial system has a certain level of development. This study is based on two secondary datasets and focuses on the Republic of Serbia, in the period of 2005-2018. The aim of this research is to determine the state of financial inclusion in the Republic of Serbia, and to test the relation between financial inclusion and carbon emissions. Based on correlation analysis, the results suggest that higher number of bank branches will result in higher CO2 emissions. Conversely, the introduction of more Automated Teller Machine (ATM) will yield lower carbon emissions. Results show that digitalization of financial transactions is enhanced, and environmental indicators are slightly decreasing. Therefore, findings suggest that digital financial inclusion in the Republic of Serbia can lead to carbon emissions reduction. Such results are important for policy makers since further digitalization can help in completing the goals of the Sustainable Development Agenda 2030.
Keywords: Digital finance, Carbon emissions, E-banking